Computational Approaches to Phonology: Advances in Speech Recognition and Synthesis - Aulia Yunus; Novi Yanti; Yani Lubis (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2023)
This article explores the field of computational approaches to phonology, with a particular focus on recent increases in popularity and speech synthesis. Phonology, as a department of linguistics, deals with the observation of sounds and their work in language. Recent improvements in this area have resulted in major improvements in accuracy and efficiency, towards the integration of deep recognition strategies together with recurrent neural networks (RNNs) and convolutional neural networks (CNNs). the models have tested the ability to capture complex phonetic patterns and decorate the overall performance of computerized speech reputation structures. These advances have seen packages in multiple domains, such as virtual assistants, text-to-speech structures, and language acquisition tools. This article looks at the main computational procedures used in phonology, along with characteristic-based representations, rule-based modes, and statistical methods. It explores demanding situations related to phonological evaluation, which include phoneme segmentation, pronunciation variants, and language-specific problems. In addition, this paper discusses mixing phonological knowledge with device learning strategies, which enables the development of robust and correct speech recognition and synthesis systems. As usual, this research represents remarkable advances from computational methods to phonology, particularly in the geographical area of speech recognition and synthesis. the combination of technology and linguistic insights has increased the accuracy, naturalness, and efficiency in processing spoken language. These enhancements open up new opportunities to enhance human-pc interaction, language recognition, and many other packages that rely on speech-based technologies.